Behavioral Advantages of the First-Person Perspective Model for Imitation - Watanabe, Rui; Higuchi, Takahiro (Frontiers in Psychology, 2016)
Visuomotor information may be better conveyed through a first-person perspective than through a third-person perspective. However, few reports have shown a clear behavioral advantage of the first-person perspective because of the confounding factor of spatial stimulus-response compatibility. Most imitation studies have utilized visuospatial imitation tasks in which participants use the same body part as that used by the model, identified by its spatial position (i.e., the response action is predefined). In such studies, visuomotor information conveyed by the model does not appear to facilitate imitative behavior. We hypothesized that the use of the first-person perspective would facilitate more efficient imitative behavior than a third-person perspective when participants are asked to choose and reproduce an action identical to that of the model rather than to select the same body part; this task requires the analysis of both visual and motor information from the model rather than a simple assessment of spatial information. To test this hypothesis, we asked 15 participants to observe a model from two perspectives (first-person and third-person) with left or right hand laterality and to lift their index finger with an identical movement type (extension or flexion) as quickly as possible. Response latencies were shorter and fewer errors were made in trials using the first-person perspective than in those using the third-person perspective, regardless of whether the model used the right or left hand. These findings suggest that visuomotor information from the first-person perspective, without confounding effects of spatial information, facilitates efficient imitative behavior.